2014
DOI: 10.3109/08820538.2014.962172
|View full text |Cite
|
Sign up to set email alerts
|

Pro Re Nata Intravitreal Bevacizumab for the Treatment of Idiopathic Choroidal Neovascular Membrane

Abstract: Intravitreal bevacizumab on a pro re nata basis is effective in the treatment of idiopathic choroidal neovascular membrane. A larger controlled study would be required to formulate an accurate injection protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Anti-VEGF therapy used at baseline and then PRN has been found comparable efficacy in most of the studies on ICNV [7,9,17,18]. Previous studies [7,15] have found that intravitreal bevacizumab on a PRN basis was effective in the treatment of ICNV and suggested that a single loading injection, followed by as-needed dosing, achieved favorable outcome. Taking Chinese current medical environment into account, we thought that the 1 + PRN regimen not only reduced the burden of patients' costs, but also reduced the risk of systemic complications caused by repeated intravitreal injections [19].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Anti-VEGF therapy used at baseline and then PRN has been found comparable efficacy in most of the studies on ICNV [7,9,17,18]. Previous studies [7,15] have found that intravitreal bevacizumab on a PRN basis was effective in the treatment of ICNV and suggested that a single loading injection, followed by as-needed dosing, achieved favorable outcome. Taking Chinese current medical environment into account, we thought that the 1 + PRN regimen not only reduced the burden of patients' costs, but also reduced the risk of systemic complications caused by repeated intravitreal injections [19].…”
Section: Discussionmentioning
confidence: 96%
“…After one intravitreal ranibizumab (IVR, 1.25 mg/0.05 ml, Novartis, Schweiz) or bevacizumab (IVB, 1.25 mg/0.05 ml, Genentech, USA) injection, patients were assessed monthly and received pro re nata (PRN) treatments until there was no sign of CNV activity based on the following criteria: no presence of subretinal/intraretinal fluid, no persistent/recurrent retinal haemorrhage or no drop in visual acuity of 5 letters, or the lesion became compact and only cicatricial CNV remained compared to the previous visits on OCT [14,15]. Either bevacizumab or ranibizumab was used as monotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike AMD, CNV lesions are smaller in patients with ICNV than in patients with AMD, with the former characterized by mild edema and less bleeding. Patients with ICNV are usually treated using the 1 + PRN treatment plan [ 24 26 ]. Conbercept, a recombinant fusion protein, can block the binding of VEGF to its receptor and inhibit the formation of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…After one intravitreal ranibizumab (IVR, 1.25 mg/0.05ml, Novartis, Schweiz) or bevacizumab (IVB, 1.25 mg/0.05ml, Genentech, USA) injection, patients were assessed monthly and received pro re nata (PRN) treatments until there was no sign of CNV activity based on the following criteria: no presence of subretinal/intraretinal fluid, no persistent/recurrent retinal haemorrhage or no drop in visual acuity of 5 letters, or the lesion became compact and only cicatricial CNV remained compared to the previous visits on OCT (14,15). Either bevacizumab or ranibizumab was used as monotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-VEGF therapy used at baseline and then PRN has been found comparable efficacy in most of the studies on ICNV (7,9,17,18). Previous studies (7,15) have found that intravitreal bevacizumab on a PRN basis was effective in the treatment of ICNV and suggested that a single loading injection, followed by as-needed dosing, achieved favorable outcome. Taking…”
Section: Comparison Between Subgroups According To Baseline Bcvamentioning
confidence: 96%